Priority action for non-governmental organization during emergency operation in Nigeria - Umar Gabarin, Abubakar; Ali, Maimunah (Associated Asia Research Foundation (AARF), 2018)
The history of how successive governments are making efforts to protect the lives and property of Nigerian citizens during emergencies/disaster situation cannot be completed without mentioning the contributions given by the Non-Governmental Organizations (NGOs). This paper traces the priority action of the NGOs during emergency situation in Nigeria based on a study of previous literature about NGOs missions as majority of the Nigerian people, especially the rural communities are in support of how NGOs are training rural skills and local knowledge that were grossly underutilized by the communities. Although, the NGOs may have the same missions but different in approaches to emergency situation. However, the study proposed to NGOs the best ways to respond to emergency situation by getting information about the location of the disaster, accessibility of the area, and to avoid duplication of efforts or clash, they also have to inquire about what other sister organizations’ are doing about same incident. It is also a priority for every NGO to make necessary arrangement of response plan according to the rule of laws.